Politics and the media : film and television for the political scientist and historian - Clark, M. J. (Audio-visual media for education and research, 1979)
Politics and the Media: Film and Television for the Political Scientist and Historian focuses on the use of film and television in the study of history and political science. Television-based history teaching in the context of the traditional university is discussed, along with the impact of broadcasting in democratic politics and the possibilities of using film in courses on American government and politics.